(untitled) - Johansson, Johny K. (Boston, 2006)
Johansson’s Global Marketing, 4/e utilizes a three-pronged framework to organize the discussion of how to conduct global business: Foreign Entry, Local Marketing, and Global Management. Johansson seeks to develop the varied skills a marketing manager needs to be successful in each of these tasks. The discussion progresses from how to market an existing product outside of the domestic market to how to develop a new product for specific local markets and then broadens the scope to discuss marketing and management topics from a global managerial perspective. Legal, regulatory, political, and cultural, issues are discussed as appropriate throughout the text. Excellent examples and cases, many of which are drawn from the author’s rich international experience, help students move from concept to application. Most International Marketing books have 6-7 separate chapters up front that discuss the legal and regulatory, political, and cultural environments before they begin to discuss global market entry. Johansson presumes that the students have a basic appreciation of these environments and begins the market entry discussion after 3 introductory chapters. The orientation of this text is more managerial and less descriptive. This text is used both as the first course in the undergraduate level and in MBA level courses.
Marketing địa phương
Keywords: Export marketing,Tiếp thị xuất khẩu; Management,Quản lý